Effect of production system on physical–chemical, antioxidant and fatty acids composition of Longissimus dorsi and Serratus ventralis muscles from Iberian pig - Tejerina, D; García-Torres, S; Cabeza de Vaca, M; Vázquez, F M; Cava, R (Food Chemistry, 2012)
The effect of three production systems of Iberian pigs namely Montanera (free-range system and feeding based on acorns and grass), Recebo (free-range system and nutrition based in combination of acorns, grass and mixed feeds) and Intensive (conﬁnement with mixed feeds) on some quality traits of Longissimus dorsi (LD) and Serratus ventralis (SV) muscles were studied. Muscles from pigs raised in the Montanera system showed signiﬁcantly higher CIE L ⁄ , a ⁄ and b ⁄ values and higher haem pigment content than those from Intensive system. Similarly, muscles from pigs raised in the Montanera system had signiﬁcantly higher contents of a and c-tocopherol and phenolic compounds contents and higher lipophilic and hydrophilic activity antioxidant than those from pigs raised in the Intensive system. Fatty acids proﬁles from Montanera pigs had signiﬁcantly higher monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids and lower saturated fatty acids (SFA) than those from pigs raised in the Intensive system. In relation to muscle effect, LD showed lower intramuscular fat (IMF), a-tocopherol, phenolic compounds, lipid oxidation and PUFA, but higher MUFA than SV.
Keywords: antioxidant; fatty acids; Iberian pigs; Montanera

Seed storage in polyethylene bags of a recalcitrant species (Quercus ilex): analysis of some bio-energetic and oxidative parameters - Pasquini, Sergio; Mizzau, Michela; Petrussa, Elisa; Braidot, Enrico; Patui, Sonia; Gorian, Fabio; Lambardi, Maurizio; Vianello, Angelo (Acta Physiologiae Plantarum, 2012)
Some technological and physiological aspects were analysed during seed storage of holm oak (Quercus ilex L.), a typical Mediterranean recalcitrant species. Considering the mild dormancy and desiccation sensitivity of these seeds, the inﬂuence of the storage environment on viability was examined. Acorns were maintained at low temperature and at high moisture content either inside thin polyethylene bags or mixed with peat in a bin. Storage in polyethylene bags, if compared with peat treatment, maintained optimal seed quality parameters. The effects of the two treatments on some physiological parameters were analysed during 1-year seed storage. Acorns stored in a bin with peat started to germinate early and exhibited a more rapid seed deterioration caused by metabolism-linked oxidative damage. The latter phenomenon was linked to a higher respiration and H2O2 level, induction of catalase activity, as well as lowered glutathione pool and ATP content. In addition, a more oxidized redox poise was observed. On the contrary, the plastic ﬁlm of polyethylene, limiting gaseous exchanges, maintained acorn metabolic activity at low levels and allowed the accumulation of ethylene inside the storage atmosphere. These factors, inducing a dormant-like state, could have played a crucial role in prolonging seed storage.
Keywords: antioxidant; ethylene; Holm oak; storage

Acorns (Quercus rotundifolia Lam.) and grass as natural sources of antioxidants and fatty acids in the “montanera” feeding of Iberian pig: Intra- and inter-annual variations - Tejerina, D.; García-Torres, S.; Cabeza de Vaca, M.; Vázquez, F. M.; Cava, R. (Food Chemistry, 2011)
In two consecutive years (2006/2007 and 2007/2008), fortnightly samples were taken to characterise the antioxidant composition and fatty acid proﬁle of acorns and grass on which Iberian pigs feed during the period of ‘‘montanera” (free-range rearing system of the south-western of Iberian Peninsula). The antioxidant parameters analysed were: a- and c-tocopherol, total phenolics compounds (TPC), lipophilic and hydrophilic antioxidant activities (LAA, HAA) (acorn and grass) and condensed and hydrolysable tannins (CT, HT) and protein precipitating capacity (PP) (acorns). To characterise the fatty acid proﬁles, the thirteen major fatty acids were assayed. For the acorns, it was found that there was intra-annual variability in all the antioxidants studied except a-tocopherol, and inter-annual variability in all except the protein precipitating capacity. The fatty acid proﬁle also varied depending on the sampling date and the study year, especially in the saturated fatty acids (SFA) and C18:1 n-9 content. For the grass, there was intraand inter-annual variability in all the antioxidant parameters studied, and in the proportions of the fatty acids C18:0, and C18:1. It could explain variations in the antioxidant and fatty acids composition of Iberian pig tissues from animals raised in different ‘‘montanera” seasons and even in the same ‘‘montanera” season.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: acorn; antioxidant; fatty acid; Grass; iberian pig; ‘‘Montanera”

Volatile organic compounds from Italian vegetation and their interaction with ozone. - Calfapietra, Carlo; Fares, Silvano; Loreto, Francesco (Environmental pollution (Barking, Essex : 1987), 2009)
Volatile Organic Compounds (VOCs) emitted from vegetation (particularly isoprenoids) represent an important source of atmospheric hydrocarbons almost double the anthropogenic source. When biogenic VOC mix with NO(x) in the presence of UV radiation, ozone (O(3)) is formed. In Italy, optimal conditions for O(3) formation in terms of VOC/NO(x) ratios and abundance of UV radiation occur for long periods of the year. Moreover, Italian vegetation includes several species that are strong and evergreen isoprenoid emitters, and high temperatures for part of the year further stimulate these temperature-dependent emissions. We review emission of isoprenoids from Italian vegetation, current knowledge on the impact of rising O(3) levels on isoprenoid emission, and evidence showing that isoprenoids can increase both the O(3) flux to the plant and protection against oxidative stress because of their antioxidant functions. This trait not only influences plant tolerance to O(3) but also may substantially alter the flux of O(3) between atmosphere and biosphere.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 19019511
Keywords: antioxidant; isoprene; Monoterpene; Ozone flux; VOC

Antioxidant properties of wood extracts and colour stability of woods - Diouf, Papa-Niokhor; Merlin, André; Perrin, Dominique (Ann. For. Sci., 2006)
Industrial wood extracts were selected and other extracts were prepared in the laboratory from some chosen wood species. Antioxidant capacities of extracts were measured by three methods: the oxygen uptake method, the kinetic DPPH method, and the equilibrium DPPH method. There is a fair correlation between the three methods. Total phenol contents of the extracts and colour stability of woods were measured. For the same phenol content, extracts containing condensed tannins are more antioxidant than those containing hydrolysable tannins. Colour stability is clearly correlated neither with phenol content nor with antioxidant capacity of the extracts, but it is conferred to non durable woods if impregnated with extracts of durable species. Light aging is accompanied by consumption of the most antioxidant compounds of the extracts first.
Keywords: antioxidant; colour; extract; polyphenol; tannin; Wood

Antioxidant properties of wood extracts and colour stability of woods - Diouf, Papa-Niokhor; Merlin, André; Perrin, Dominique (Ann. For. Sci., 2006)
Industrial wood extracts were selected and other extracts were prepared in the laboratory from some chosen wood species. Antioxidant capacities of extracts were measured by three methods: the oxygen uptake method, the kinetic DPPH method, and the equilibrium DPPH method. There is a fair correlation between the three methods. Total phenol contents of the extracts and colour stability of woods were measured. For the same phenol content, extracts containing condensed tannins are more antioxidant than those containing hydrolysable tannins. Colour stability is clearly correlated neither with phenol content nor with antioxidant capacity of the extracts, but it is conferred to non durable woods if impregnated with extracts of durable species. Light aging is accompanied by consumption of the most antioxidant compounds of the extracts first.
Keywords: antioxidant; colour; extract; polyphenol; tannin; Wood